Belenggu Kepemimpinan Perempuan Dalam Ranah Politik - Zulfa, Kholid (Sunan Kalijaga State Islamic University & The Asia Foundation, 2004)
The willingnessto rest women and men in a parallel position within various aspects of life is gaining its prominence, especially in terms of women's participation in politics. Withinthe discourse ofleadership, none of the theory claims that certain sex -male or female- has more authority or privilege over another. Both sexes have the same rights to be leaders depending on who has better quality to hold that position. This article is an attempt to explain the discourse on the leadership of women within the political realm. The stigma given to women that a good woman is the ones who could perform their duties as a wife and a mother, coupled with the assumptionthat politics is dirty and full of intrigues, have weaken the opportunity of women to be actively involved in politics. For that reason, even though the number of women in Indonesia outweighs those of men, the representative of women in the parliament in every general election is only between 8 to 12 percent.